PENGARUH PENGELOLAAN KEUANGAN DAN MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN PENDAPATAN BAKSO GAWE LEGO - Alviani, Indra; Fatimah, Vidya (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to determine the effect of financial management and human resource management on the increase in the gawe lego meatball. There are two independent variables, namely Financial Management and Human Resource Management, and the dependent variable, namely Income. The method used in this study using a quantitative approach. The analysis technique applied in this study is multiple linear regression. This study used data collection methods by distributing questionnaires to respondents, and the data that had been collected was then processed using SPSS 25. The results of the study show that the variables of financial management and human resource management have a positive and significant effect on the income of Bakso gawe lego.